The Rise and Fall of Theatre NO99 in Estonia: A Case of Political and Discursive Change - Toome, Hedi-Liis (Nordic Theatre Studies, 2023)
The article focuses on the establishment and closing down of Theatre NO99 (2005-2018), one of the most nationally and internationally acclaimed theatres of Estonia. These events are analysed from two perspectives: (1) the political, because in both cases the Estonian Ministry of Culture made quite radical decisions that had a strong effect for the theatre field in general; (2) the discursive, to understand how NO99 legitimized its beginning and justified the ending. The latter is compared to the discourse of the written media to understand the dialogue between these two discourses. Pierre Bourdieu’s field theory is used to show how the external and internal forces influenced the position taking of NO99 in the Estonian theatre field and how paradoxical and even impossible it is for an avant-garde state theatre to balance between autonomous and heteronomous principals of hierarchization.